A 2-tier fuzzy control system for grade adjustment based on students' social interactions. (1st October 2022) - Krouska, Akrivi; Troussas, Christos; Voulodimos, Athanasios; Sgouropoulou, Cleo
Highlights: 2-tier fuzzy system for adjusting student final grade based on social interactions. Providing a more accurate and fairer grading system. Grade adjustment reflects the overall student performance in the learning process. Grade adjustment using social interactions promotes student engagement. Abstract: The advent of social networking platforms has opened new horizons in the field of digital education. The research effort in this field is still in its infancy and many aspects remain unexplored. For instance, in traditional classrooms, tutors compute students' final grade based on several external factors, such as their effort, participation, etc. However, according to the related literature, e-learning systems do not sufficiently follow this rationale providing solely the average score of the chapters' tests. To fill this gap, this paper introduces a two-tier fuzzy controller for recommending a readjustment of the students' final grade based on their social interactions. More specifically, the first tier of the module dynamically diagnoses the degree of students' participation, while the second tier offers a recommendation for adjustment of the students' grade. In this way, the grading is more accurate and fairer, reflecting the overall student performance throughout the learning process. Our approach was evaluated from several perspectives to ensure the effective use of the system and its positive impact on learners. The findings reveal that this novel module provides a more precise and rightful grading system, promoting student engagement.